Knowledge, Attitude and Preferred Method of Family Planning among Men Living in an Urban Slum in Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Male involvement in family planning (FP) has a direct influence on their spouse’s attitude towards the use of modern contraceptives.Aims:The aim was to determine the knowledge, attitude and preferred methods of FP among men living in an urban slum of Kano, Nigeria.Materials and Methods:A cross-sectional design was used to study 110 married men living in Dorayi Quarters in Kano. Data were obtained using interviewer-administered questionnaire. Descriptive statistics were used to describe categorical variables.P